ВЛИЯНИЕ СЕНСИТИВНОСТИ НА КОГНИТИВНОЕ РАЗВИТИЕ МЛАДШИХ ШКОЛЬНИКОВ - Турсунов, Л.С. (SCIENCE and SOCIETY, 2025)
In this article, devoted to the influence of reason on the cognitive development of a child, as well as the role of knowledge in the acquisition of knowledge, special attention is paid to the mental ontogenesis of primary school children.
Keywords: mind; non-intelligence; contemplation; perception; fantasy; memory; thinking; ontogenesis; activity; unconsciousness; awareness; knowledge; imitation; interest; ability